2018
DOI: 10.1016/j.ebiom.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling balances adult distal lung epithelial progenitor cell growth and differentiation

Abstract: BackgroundDespite compelling data describing pro-regenerative effects of all-trans retinoic acid (ATRA) in pre-clinical models of chronic obstructive pulmonary disease (COPD), clinical trials using retinoids for emphysema patients have failed. Crucial information about the specific role of RA signaling in adult rodent and human lung epithelial progenitor cells is largely missing.MethodsAdult lung organoid cultures were generated from isolated primary mouse and human lung epithelial cells, and incubated with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 91 publications
(198 reference statements)
3
93
0
Order By: Relevance
“…Notwithstanding even more advanced technologies are already pursued such as more complex 3D organ‐specific cell structures representing functional organ units (organoids) and the integration of organ‐specific chips/organoids into in vitro organism systems. Although these methods are still in an early stage, they hold the promise to overcome remaining shortcomings of current advanced in vitro models of the lung such as failure of fully mimicking the complexity of the 3D alveolar structure, the multicell interplay in the lung (≈60 different cell types) and inter‐organ connectedness via blood circulation …”
Section: Future Directions: Biomimetic Models Of the Lungmentioning
confidence: 99%
“…Notwithstanding even more advanced technologies are already pursued such as more complex 3D organ‐specific cell structures representing functional organ units (organoids) and the integration of organ‐specific chips/organoids into in vitro organism systems. Although these methods are still in an early stage, they hold the promise to overcome remaining shortcomings of current advanced in vitro models of the lung such as failure of fully mimicking the complexity of the 3D alveolar structure, the multicell interplay in the lung (≈60 different cell types) and inter‐organ connectedness via blood circulation …”
Section: Future Directions: Biomimetic Models Of the Lungmentioning
confidence: 99%
“…It was considered that this down-regulation of ST2 was attributed to the decrease in the expression of PPARγ by FABP5deficiency or knockdown, since PPARγ is involved in ST2 regulation 41 . Retinoic acid, a metabolite of vitamin A, is known to be involved in maintaining homeostasis of epithelial and mucosal tissues and regulating immune responses [42][43][44] . Although it has been reported that vitamin A supplementation induces aggravation of asthma in a mouse experimental model, the fact that RA suppresses allergic lung diseases, such as asthma is now widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid, a metabolite of vitamin A, is known to be involved in maintaining homeostasis of epithelial and mucosal tissues and regulating immune responses 42 44 . Although it has been reported that vitamin A supplementation induces aggravation of asthma in a mouse experimental model, the fact that RA suppresses allergic lung diseases, such as asthma is now widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious benefit of ex vivo organoid culture is that a capillary network usually develops over the spheroid structures, which is not seen in in vitro assays. Human distal EpCAM + epithelial cells, including AT2 cells, can be isolated from peripheral lung tissue specimens by magnetic bead sorting (MACS) [44]. Coculture of these EpCAM + cells with MRC5 human lung fibroblasts in Matrigel resulted in the formation of organoids that allows airway differentiation but not alveolar differentiation [44].…”
Section: Development Of Alveolar Organoidsmentioning
confidence: 99%
“…Human distal EpCAM + epithelial cells, including AT2 cells, can be isolated from peripheral lung tissue specimens by magnetic bead sorting (MACS) [44]. Coculture of these EpCAM + cells with MRC5 human lung fibroblasts in Matrigel resulted in the formation of organoids that allows airway differentiation but not alveolar differentiation [44]. Alveolar differentiation was promoted by inhibiting TGF-β receptor signaling in organoids derived from human distal airway ΔNp63 + TTF-1 + stem cells [40].…”
Section: Development Of Alveolar Organoidsmentioning
confidence: 99%